Abscess and pulmonary tuberculosis - Hercelles García, Oswaldo (1937)
If pulmonary tuberculosis has been known since ancient times and lung abscess is considered, since the nineteenth century as a well-defined disease entity, it is clear that the abscess association and pulmonary tuberculosis has not its true expression study, but recent years.